Self Adjustment of Adolescents in the Orphanage Parupuk Tabing - Yoga Pratama; Firman Firman (Jurnal Neo Konseling, 2021)
Self-adjustment is the alignment made by individuals to the environment both peer and social environments, and wherever the individual is, to be able to live a life that is appropriate and to be able to meet the demands of that environment. As for the aspects of self-adjustment according to (Sobur, 2013), namely personal adjustment and social adjustment. Self-adjustment is related to (the individual's ability to accept himself so as to achieve a harmonious relationship between himself and the surrounding environment. This study aims to (1) describe the adjustment of adolescents to peers at the Al-Falah Parupuk Tabing orphanage, (2) describe the adjustment of adolescents to their environment at the Al-Falah Parupuk Tabing orphanage. This type of research is a descriptive study using quantitative methods. The research subjects were 34 teenagers in the Al-Falah Parupuk Tabing Padang orphanage. The findings of the study revealed that (1) the adjustment of adolescents in the Al-Falah Parupuk Tabing orphanage was generally in the low category, (2) Adolescent adjustment at the Al-Falah Parupuk Tabing orphanage, seen from the aspect of personal adjustment, is in the medium category, 3) Adolescent adjustment in the Al-Falah Parupuk Tabing orphanage, seen from the aspect of social adjustment, is in the low and high categories.